2006
DOI: 10.1142/s0217979206034352
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Relations for a Deformed Oscillator

Abstract: We construct a deformed oscillator whose energy spectra is similar to that of a Morse potential. We obtain a convenient algebraic representation of the displacement and the momentum of a Morse oscillator by expanding them in terms of deformed creation and annihilation operators and we compute their average values between approximate coherent states of the deformed oscillator, and we compare them to the results obtained using the exact Morse coordinate and momenta. Finally we evaluate the temporal evolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…We also evaluated the dispersions in the deformed coordinate and momentum between nonlinear coherent states obtained with the displacement operator D D (α). In [22] we evaluated them between Morse-like approximate coherent states obtained as eigenstates of the deformed annihilation operator and found that these approximate coherent states were not minimum uncertainty states though they showed a periodic behaviour with an amplitude near that of a minimum uncertainty state. Figure 4 shows the temporal evolution of the average value of the deformed coordinate D α|x D (t)|α D (upper panel) and in the lower panel we show the corresponding normalized dispersion 2 x D p D /| [x D , p D ] | and the dispersion in the momentum p D for fixed α = 0.5 and a system supporting N = 10 bound states.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We also evaluated the dispersions in the deformed coordinate and momentum between nonlinear coherent states obtained with the displacement operator D D (α). In [22] we evaluated them between Morse-like approximate coherent states obtained as eigenstates of the deformed annihilation operator and found that these approximate coherent states were not minimum uncertainty states though they showed a periodic behaviour with an amplitude near that of a minimum uncertainty state. Figure 4 shows the temporal evolution of the average value of the deformed coordinate D α|x D (t)|α D (upper panel) and in the lower panel we show the corresponding normalized dispersion 2 x D p D /| [x D , p D ] | and the dispersion in the momentum p D for fixed α = 0.5 and a system supporting N = 10 bound states.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…appears in the numerator in one case and in the denominator in the other. It was shown in [22] that the average value of the position and momentum operators pertinent to a Morse-like potential taken between the coherent states given in (25) present a conduct that resembles very closely the classical one. In this section we evaluate the averages of position and momentum for a Morse-like potential between the coherent states obtained via the displacement operator and present a comparison between them.…”
Section: Average Valuesmentioning
confidence: 97%
See 3 more Smart Citations